Amylin structure–function relationships and receptor pharmacology: implications for amylin mimetic drug development. (18th May 2016) - Bower, Rebekah L; Hay, Debbie L
Abstract : Amylin is an important, but poorly understood, 37 amino acid glucoregulatory hormone with great potential to target metabolic diseases. A working example that the amylin system is one worth developing is the FDA‐approved drug used in insulin‐requiring diabetic patients, pramlintide. However, certain characteristics of pramlintide pharmacokinetics and formulation leave considerable room for further development of amylin‐mimetic compounds. Given that amylin‐mimetic drug design and development is an active area of research, surprisingly little is known about the structure/function relationships of amylin. This is largely due to the unfavourable aggregative and solubility properties of the native peptide sequence, which are further complicated by the composition of amylin receptors. These are complexes of the calcitonin receptor with receptor activity‐modifying proteins. This review explores what is known of the structure–function relationships of amylin and provides insights that can be drawn from the closely related peptide, CGRP. We also describe how this information is aiding the development of more potent and stable amylin mimetics, including peptide hybrids.